Finding Solutions for Productive Waqf Management in Indonesia - Ulfa, Nur Nazima; Mustafa, Muhammad Isa (SMART Insight, 2023)
Waqf has a contribution to the economic development of a country, which can reduce government spending, equalize income distribution, reduce poverty and can increase economic growth. However, at present the potential for waqf has not been used optimally in Indonesia. There are many factors that cause not optimal management of waqf, therefore the author tries to analyze the management of productive waqf in Indonesia seen from 3 elements: problem elements, strategic elements, and institutional / stakeholder elements using Interpretive Structural Modeling (ISM) and the Delphi method. The results of this study of elements of problems which are the highest ranks are the less of educational or public understanding of waqf, less of public trust in Nazhir institutions and weak political will of authority holders. While the highest ranking of the elements of the strategy is the support of regulations / legislation on law. Then the highest rank of the related institutional elements are BWI, Ministry of Religious Affair (MoRA), and DSN-MUI.